Edukasi Gout Arthritis dan Senam Ergonomik untuk Meningkatkan Pengetahuan Serta Kesehatan Lansia di Panti Wening Wardoyo Ungaran - Al Hajar Fuadatus Zurroh; Melati Aprilliana Ramadhani; Ika Nilawati; Dwi Retna Susilowati (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Gout Arthritis is a form of arthritis that often occurs in the elderly, especially due to an unhealthy lifestyle and lack of physical activity. Health education and physical interventions such as ergonomic exercises can be effective strategies to improve the understanding and health conditions of the elderly. This community service activity aims to provide education about Gout Arthritis and ergonomic exercises in improving the knowledge and health of the elderly at Panti Wening Wardoyo, Ungaran. A total of 48 elderly people participated in educational activities and ergonomic exercise practices. Participants' knowledge was measured using a multiple choice question instrument before (pretest) and after (posttest) the intervention. The pretest results showed that 8.33% of participants were in the "Very Good" category, 45.83% "Good", 33.33% "Fair", and 12.50% "Poor". After being given education, the post test results showed a significant improvement, with 72.92% of participants in the "Very Good" category and 27.08% in the "Good" category. There were no participants who were in the "Enough" or "Poor" categories in the post test. Education regarding Gout Arthritis and ergonomic exercises has proven to be effective in increasing the knowledge of the elderly and is recommended to be implemented on an ongoing basis in promotive and preventive efforts in social care environments.     ABSTRAK Gout Arthritis merupakan salah satu bentuk arthritis yang sering terjadi pada lanjut usia (lansia), terutama akibat gaya hidup yang tidak sehat dan kurangnya aktivitas fisik. Edukasi kesehatan dan intervensi fisik seperti senam ergonomik dapat menjadi strategi efektif untuk meningkatkan pemahaman serta kondisi kesehatan lansia. Kegiatan pengabdian kepada masyarakat ini merupakan kegiatan yang dilaksanakan oleh Dosen Program Studi Farmasi, Dosen program studi PJOK dan dibantu oleh mahasiswa farmasi yang bertujuan untuk memberikan edukasi tentang Gout Arthritis dan senam ergonomik dalam meningkatkan pengetahuan serta kesehatan lansia di Panti Wening Wardoyo, Ungaran. Sebanyak 48 lansia menjadi partisipan dalam kegiatan edukasi dan praktik senam ergonomik. Pengetahuan peserta diukur menggunakan instrumen soal pilihan ganda sebelum (pretest) dan sesudah intervensi (post test). Hasil pretest menunjukkan bahwa 8,33% peserta berada dalam kategori "Sangat Baik", 45,83% "Baik", 33,33% "Cukup", dan 12,50% "Kurang". Setelah diberikan edukasi, hasil post test menunjukkan peningkatan signifikan, dengan 72,92% peserta berada dalam kategori "Sangat Baik" dan 27,08% dalam kategori "Baik". Tidak ada peserta yang berada dalam kategori "Cukup" maupun "Kurang" pada post test. Edukasi mengenai Gout Arthritis dan senam ergonomik terbukti efektif dalam meningkatkan pengetahuan lansia dan disarankan untuk diterapkan secara berkelanjutan dalam upaya promotif dan preventif di lingkungan panti sosial.